CLINICAL AND INSTRUMENTAL CHARACTERISTICS OF AXIAL LESION IN EARLY PERIPHERAL PSORIATIC ARTHRITIS (DATA OF A REMARCA STUDY) - E. E. Gubar; E. Yu. Loginova; A. V. Smirnov; S. I. Glukhova; T. V. Korotaeva; E. L. Nasonov (Научно-практическая ревматология)
Objective: to investigate the extent of axial skeleton lesion in a Russian cohort of patients with early peripheral psoriatic arthritis (epPsA).Subjects and methods. Examinations were made in 89 patients (42 men and 47 women) (mean age, 36.5±10.9 years) with epPsA (duration, 12.1±10.1 months), the diagnosis of which met the CASPAR criteria. In addition to the standard examination, all the patients underwent evaluation of inflammatory back pain (IBP) (ASAS criteria), pelvic radiography, and determination of HLA-B27; 79 patients had additionally magnetic resonance imaging (MRI) of the sacroiliac joints (AIJ). Active sacroiliitis (SI) detected on MRI (MRI SI) was defined as bone marrow edema (osteitis) on T2 STIR. SI on radiography (rSI) was recorded if there were changes in at least one AIJ of Kellgren grade 2 or higher; radiologically significant SI (rsSI) was diagnosed when there were changes in the AIJ, which corresponded to its lesion in ankylosing spondylitis (grade II and higher bilateral SI or grade III and higher unilateral SI). The results of radiography and MRI were assessed by an independent radiologist. The disease activity in patients with IBP was evaluated by BASDAI.Results and discussion. IBP was identified in 58 (65.1%) patients; it was episodic in 35 (60.3%) and permanent in 23 (39.7%) cases. There was MRI SI in 28 (35.4%) of the 79 patients, rSI in 42 (47.2%), rsSI in 27 (30.3%) cases. 34 (38.1%) of the 84 patients were HLA-B27 positive. The mean BASDAI value was 4.5±1.6. An association was found between the presence of MRI SI and IBP: IBP was present in 92.9% of the patients with MRI SI and in 54.9% of those without MRI SI (p=0.0002). There is a relationship of MRI SI to permanent IBP (p=0.003). An association was found between the presence of rSI and IBP (p=0.047), between rSI and permanent IBP (p=0.01) and between rsSI and IBP (p=0.01). At the same time, SI was asymptomatic in 23.8% of the patients: rSI developed without previous IBP. No association was found between MRI SI/rSI/rsSI and HLA-B27. There was an association between MRI SI and higher peripheral arthritis activity by the DAS28. The mean DAS28 value was 9.34±1.79 in patients with MRI SI and 8.57±1.63 in those without MRI SI (r=0.25; p=0.028). There was an association between the presence of MRI SI and the values of disease activity assessment by a patient (r=0.23; p=0.047) and those of pain assessment by a patient (r=0.31; p=0.0074). An association was found between MRI SI and the affected area of the skin.Conclusion. In epPsA, there is IBP in 65% of the patients (it was episodic in 60% of them), MRI SI in 35%, rSI in 47.2%, and rsSI in 30.3%. There is an association between IBP and SI detected by any of the imaging techniques (MRI and radiography). In 24% of patients, rSI developed without previous IBP, suggesting that there is latent axial lesion. MRI SI is more frequently detected in patients having higher arthritis activity by the DAS28, higher overall disease and pain assessments by the patient, and a large area of skin lesions.